EVALUASI KEBIJAKAN PERATURAN DAERAH NOMOR 5 TAHUN 2007 TENTANG LARANGAN PELACURAN DI KABUPATEN BANTUL PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Astri Candra Dewi; Ridho Al-Hamdi (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2020)
This paper analyzes the driving factors determining the failure of the local regulation Number 5 Year 2007 regarding the prostitution prohibition in Bantul Regency, Yogyakarta Special Territory by explaining the evaluation toward this regulation. Methodologically, this study utilizes qualitative method with a case study approach. To gather data, it employs documentation study and in-depth interview. As an analytical framework, this study adopts six indicators the policy evaluation developed by William Dunn, namely effectiveness, efficiency, adequacy, responsiveness, equality, and appropriateness. The finding reveals that among six indicators, three are classified as the failed indicator and the rest is successful. Nevertheless, there are three fundamental indicators which determine that this regulation will be a successful policy, i.e. effectiveness, adequacy, and responsiveness. It can be concluded that the evaluation to this regulation denotes a failed regulation. Therefore, the local government needs to take serious efforts to increase the implementation of the policy.